2004
DOI: 10.1111/j.1463-1318.2004.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

3 years follow‐up of a twisted ileoanal pouch

Abstract: contolled trial including incontinence scoring, anorectal manometry and endoanal ultrasound assessment at up to three months. Dis Colon Rectum 2000; 12: 1666-75. 5 Thaha MA, Kazini SA, Irvine LA et al. New onset faecal urgency and its impact on recovery following circular stapled anopexy: preliminary results of a multicentre randomised controlled trial. Br J Surg 2003; 90 (Suppl.): 65 (Abstract). 6 Quah HM, Hadi HIA, Hay DJ, Maw A. Residual staples as a possible cause of recurrent rectal bleeding after stapled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The flow diagram of different phases of this systematic review is shown in Figure 1. We identified 16 publications from nine countries published between 1993 and 2018 that met the selection criteria [14–29] and we reported an additional case from the Mayo Clinic identified in the database search. Thirteen studies were found by the librarian search, two by the Google Scholar search [14, 19], and one from reference lists of relevant papers [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow diagram of different phases of this systematic review is shown in Figure 1. We identified 16 publications from nine countries published between 1993 and 2018 that met the selection criteria [14–29] and we reported an additional case from the Mayo Clinic identified in the database search. Thirteen studies were found by the librarian search, two by the Google Scholar search [14, 19], and one from reference lists of relevant papers [28].…”
Section: Resultsmentioning
confidence: 99%
“…All the publications were in English. Two publications were in abstract form [22, 27], four were letters to the editor [14, 16, 23, 24], and the remaining were full-text articles. There was one case series reporting six patients [26] and 15 case reports reporting one patient each.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of this condition typically requires a high degree of suspicion, CT, and gastrografin enema. The patients reported in the literature have been managed surgically with adhesiolysis and derotation and fixing the pouch with or without revision of the ileorectal anastomosis [ 5 , 6 , 8 , 9 ]. Twists can be managed with an endoscopic approach, which avoids the need for a large open surgical procedure that can be technically challenging due to severe adhesions and might lead to increased complications and prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis is a chronic idiopathic inflammatory disease of the colorectal mucosa. This disease affects approximately 500,000 to 1,000,000 people in the United States [2][3][4][5]; 25% -33% of whom require some form of surgical treatment [6]. Restorative proctocolectomy with ileal pouch anal anastomosis is the surgical treatment of a choice in patients with medically refractory disease or evidence of dysplasia.…”
Section: Introductionmentioning
confidence: 99%